Relationship between the elbow joint valgus instability and forearm flexor muscle strength in high school pitchers with and without symptom. (1st March 2019) - Tajika, Tsuyoshi; Oya, Noboru; Ichinose, Tsuyoshi; Shimoyama, Daisuke; Sasaki, Tsuyoshi; Hamano, Noritaka; Shitara, Hitoshi; Yamamoto, Atsushi; Takagishi, Kenji; Chikuda, Hirotaka
Objectives: Earlier reports describe forearm flexor muscles as active stabilizers of the elbow to valgus stress during throwing motion. Given high school pitchers' history of elbow symptoms, this study assesses its relation to elbow valgus joint instability and forearm flexor muscle strength. Methods: Ultrasound examination was made for 132 high school baseball pitchers with and without valgus stress of the medial aspect of the bilateral elbows. They had completed a self-administered questionnaire related to self-satisfaction score (0–100) for pitching performance and throwing-related elbow joint pain sustained during the prior year. Using a digital manual muscle strength meter, we examined the grip strength and muscle strength of the flexor carpi ulnaris (FCU). For participants with and without a history of elbow symptom, we compared differences of ulnohumeral joint space width with and without valgus stress and grip and FCU muscle strength. Results: For ulnohumeral joint width difference with and without valgus stress, pitchers with an elbow symptom and those without elbow symptom history on the throwing side were not significantly different. No difference was found in the grip strength or FCU muscle strength of the throwing side for each group. Positive significant association was found between FCU muscle strength on the pitching side and the self-evaluation score for pitching performance ( r = 0.27, p = 0.002). However, no association was found between the elbow valgus instability and the forearm flexor muscle strength. Conclusion: FCU muscle strength might influence high school baseball pitching performance.